Derivational Suffixes in the Novel A Little Princess - Pramesti, Ni Kadek Pramudhea Ayu; Aryani, I Gusti Agung Istri; Indrawati, Ni Luh Ketut Mas (UPT Publikasi dan Penerbitan Universitas San Pedro, 2025)
This research focuses on the use of derivational suffixes in the novel A Little Princess by Frances Hodgson Burnett. This study aims to identify the types of derivational suffixes and explain how derivational suffixes found influence the class-changing transformations in the novel A Little Princess. Data were collected through documentation method and note-taking technique. In analyzing the data, this research using descriptive qualitative methods. The analysis refers to Plag's (2003) and Bauer's (1983) theories. A total of 161 derivational suffixes were found in the novel. The suffixes include four types: nominal, verbal, adjective, and adverbial suffixes. The most frequently used adverbial suffix is -ly, which appears 64 data. This suffix generally functions to describe the way or attitude in an action or situation. The results also show two types of derivational effects: class-maintaining and class-changing derivation. Class-changing derivation are dominant, with 158 data, while class-maintaining derivation only occurs 3 data. These results highlight the important role of derivational suffixes in enriching vocabulary and forming grammatical structures in literary texts.